2020
DOI: 10.1016/j.jvs.2019.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Functional ambulatory status as a potential adjunctive decision-making tool following wound, level of ischemia, and severity of foot infection assessment

Abstract: The Society for Vascular Surgery Lower Extremity Threatened Limb Classification System has been developed to stratify amputation risk on the basis of extent of the wound, level of ischemia, and severity of foot infection (WIfI). However, there are no currently validated metrics to assess, grade, and consider functional status, especially ambulatory status, as a major consideration during limb salvage efforts. Therefore, we propose an adjunct to the current WIfI system to include the patient's ambulatory functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Additionally, in the present study, homicide rates also were associated with amputation rates in unadjusted analysis, suggesting a potential association of safety perception and engagement with physical exercise . The association between physical activity and amputation may also be attributable to surgeon decision-making, as ambulatory status is an important component of patient-centered limb preservation risk-benefit analysis . The absence of an association between physical inactivity and amputation in the adjusted analysis also suggested that the findings in the unadjusted analysis may be associated with the presence of confounding variables, such as neighborhood safety and physical stress levels, which were found to be associated with amputation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the present study, homicide rates also were associated with amputation rates in unadjusted analysis, suggesting a potential association of safety perception and engagement with physical exercise . The association between physical activity and amputation may also be attributable to surgeon decision-making, as ambulatory status is an important component of patient-centered limb preservation risk-benefit analysis . The absence of an association between physical inactivity and amputation in the adjusted analysis also suggested that the findings in the unadjusted analysis may be associated with the presence of confounding variables, such as neighborhood safety and physical stress levels, which were found to be associated with amputation rate.…”
Section: Discussionmentioning
confidence: 99%
“…26 The association between physical activity and amputation may also be attributable to surgeon decision-making, as ambulatory status is an important component of patient-centered limb preservation risk-benefit analysis. 57 The absence of an association between physical inactivity and amputation in the adjusted analysis also suggested that the findings in the unadjusted analysis may be associated with the presence of confounding variables, such as neighborhood safety and physical stress levels, which were found to be associated with amputation rate. Overall, these findings highlight the importance of implementation of policies in these communities to target physical activity engagement (eg, parks, sidewalks, bike lanes, and overall public safety), ensuring a safe environment for such activities while reducing stressors that may be inhibitory.…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular disease and inadequate glycemic control are the main factors. Sociodemographic factors appear to be critical in the emergence of diabetic foot ulcers (Khan, et al, 2020). Treatment also plays a big role in reducing the risk of the lipid profile, especially after the patient's diagnosis with DFU.…”
Section: Discussionmentioning
confidence: 99%
“…However, this would certainly be valuable to assess in future studies. 7,42,43 Perhaps factors not known at the initial evaluation such as specifics of the revascularization Journal of Vascular Surgery attempt and anatomic details of the injury that were not included in the present study might provide additional information that will be of benefit. Because our stated aim was to provide an easy-to-use, practical tool for risk stratification preoperatively, the factors found intraoperatively (eg, nerve transection) were not included in the present analysis.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 99%